Differential Responses of the Egg-Larval Parasitoid Chelonus Bifoveolatus To Fall Armyworm-Induced and Constitutive Volatiles of Diverse Maize Genotypes - Collins O. Onjura; Emmanuel Peter; George O. Asudi; Michael M. Gicheru; Samira A. Mohamed; Toby J. A. Bruce; Amanuel Tamiru (Journal of Chemical Ecology, 2025)
The fall armyworm (FAW), Spodoptera frugiperda , is a serious invasive crop pest and threat to food security. Conventional pest control approaches using chemical pesticides can lead to adverse environmental and human health problems calling for safer alternative pest management options. Volatile organic compounds (VOCs) released by plants constitutively and in response to herbivory have been shown to enhance ecologically benign biocontrol alternatives to chemical insecticides for pest management. However, genotypic variations in VOC emissions have also been reported for plant species including maize ( Zea mays ). Hence, a better insight into the variations in odor profiles of different maize varieties and their corresponding role in recruiting pests’ natural enemies are crucial for developing a sustainable biocontrol strategy. Our present study assessed the behavioral responses of the FAW egg-larval parasitoid, Chelonus bifoveolatus (Braconidae: Hymenoptera), to constitutive and induced volatiles from different maize landraces (Jowi Red, Nyamula) and hybrids (SC Duma, DK 777) grown in Kenya and compared their volatile profiles. In a four-arm olfactometer, female parasitoid wasps were significantly attracted to FAW oviposition-induced VOCs from SC Duma and Nyamula. Chemical analysis of test plant volatiles revealed significant variation in the quantity and quality of key bioactive VOCs such as ( E )-2-hexenal, α-pinene, ( Z )-3-hexenyl acetate, ( E )-4,8-dimethyl-1,3,7-nonatriene, α-copaene, ( E) -β-farnesene and ( E , E )-4,8,12-trimethyl-1,3,7,11-tridecatetraene. Our findings provide more insights into genetic variation in VOCs emission across maize genotypes and the corresponding differences in attraction of pest natural enemies that provide indirect defense. As such, these traits could be exploited to enhance ecologically sustainable pest management strategies.

A novel knockout mouse for the small EDRK-rich factor 2 (Serf2) showing developmental and other deficits - Karen Cleverley; Weaverly Colleen Lee; Paige Mumford; Toby Collins; Matthew Rickman; Thomas J. Cunningham; James Cleak; Joffrey Mianne; Zsombor Szoke-Kovacs; Michelle Stewart; Lydia Teboul; Cheryl Maduro; et al. (Mammalian Genome, 2021)
The small EDRK-rich factor 2 (SERF2) is a highly conserved protein that modifies amyloid fibre assembly in vitro and promotes protein misfolding. However, the role of SERF2 in regulating age-related proteotoxicity remains largely unexplored due to a lack of in vivo models. Here, we report the generation of Serf2 knockout mice using an ES cell targeting approach, with Serf2 knockout alleles being bred onto different defined genetic backgrounds. We highlight phenotyping data from heterozygous Serf2 +/− mice, including unexpected male-specific phenotypes in startle response and pre-pulse inhibition. We report embryonic lethality in Serf2 −/− null animals when bred onto a C57BL/6 N background. However, homozygous null animals were viable on a mixed genetic background and, remarkably, developed without obvious abnormalities. The Serf2 knockout mice provide a powerful tool to further investigate the role of SERF2 protein in previously unexplored pathophysiological pathways in the context of a whole organism.

Surviving Heatwaves: Thermal Experience Predicts Life and Death in a Southern Ocean Diatom - Toby Samuels; Tatiana A. Rynearson; Sinéad Collins (Frontiers in Marine Science, 2021)
Extreme environmental fluctuations such as marine heatwaves (MHWs) can have devastating effects on ecosystem health and functioning through rapid population declines and destabilization of trophic interactions. However, recent studies have highlighted that population tolerance to MHWs is variable, with some populations even benefitting from MHWs. A number of factors can explain variation in responses between populations including their genetic variation, previous thermal experience and the cumulative heatwave intensity (°C d) of the heatwave itself. We disentangle the contributions of these factors on population mortality and post-heatwave growth rates by experimentally simulating heatwaves (7.5 or 9.2°C, for up to 9 days) for three genotypes of the Southern Ocean diatom Actinocyclus actinochilus . The effects of simulated heatwaves on mortality and population growth rates varied with genotype, thermal experience and the cumulative intensity of the heatwave itself. Firstly, hotter and longer heatwaves increased mortality and decreased post-heatwave growth rates relative to milder, shorter heatwaves. Secondly, growth above the thermal optimum before heatwaves exacerbated heatwave-associated negative effects, leading to increased mortality during heatwaves and slower growth after heatwaves. Thirdly, hotter and longer heatwaves resulted in more pronounced changes to thermal optima (T opt ) immediately following heatwaves. Finally, there is substantial intraspecific variation in post-heatwave growth rates. Our findings shed light on the potential of Southern Ocean diatoms to tolerate MHWs, which will increase both in frequency and in intensity under future climate change.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)